Chemical Characterization and Antibacterial Activities of Bio-oil from Durian Shell Pyrolysis - Mashuni, Mashuni; Kadidae, La Ode; Jahiding, M; Hamid, Fitri Handayani; Kadir, Waris Abdul; Khaeri, Andi Muhammad Naufal (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2024)
Foodborne bacteria cause food spoilage, usually Staphylococcus aureus and Escherichia coli. Thus, synthetic preservatives are employed in food preservation to prevent food spoilage caused by microorganisms. Excessive use of synthetic preservatives can cause disease. Bio-oil has become a natural preservative because of its high phenolic content. However, bio-oil still requires purification because the initial bio-oil (grade 3) still contains carcinogenic compounds that are dangerous for consumption. Therefore, this study aims to determine the components of the bio-oil compound after purification and its effectiveness as an antibacterial. Durian shell (DS) is pyrolyzed in a heating reactor without oxygen at a temperature of 330–600ºC (flow rate 6ºC/minute) with a 2-3 cm material size. Furthermore, bio-oil purification includes stages of filtration using activated zeolite, fractional distillation at 70–200ºC (grade 2), and filtration using activated charcoal (grade 1). Bio-oil purification includes stages of filtration using active zeolite and activated charcoal (grade 2), and fractional distillation at a temperature of 150–200ºC (grade 1). Based on Gas Chromatography-Mass Spectrometry (GC-MS) analysis, grade 2 and grade 1 contain the major compounds 1,4-dimethyl-1h-imidazole and acetic acid. The research showed that bio-oil grades 1 and 2, when used at a 30% concentration, exhibit antibacterial strong effects against Staphylococcus aureus and Escherichia coli. These findings suggest that bio-oil grades 1 and 2 could be valuable natural preservatives.